The 8088 and 8086 microprocessor: programming interfacing, software, hardware and applications - Triebel, Walter A.; Singh, Avtar (New Delhi : Prentice Hall of India, 2006)
Computer Science
Keywords: 8088 Micorprocessor; Programming and interfacing; Software and hardware; Software architecture; 8086 microprocessor; Machine language; Assembly language; Real mode software